REALITAS AKTUAL PRAKSIS KURIKULUM: Analisis terhadap KBK, KTSP dan Kurikulum 2013 - Loeziana Uce (Jurnal Ilmiah Didaktika, 2016)
Curriculum is one of important elements in education that need to be designed well in order to succeed teaching and learning process in schools. The meaning of praxis of curriculum is closely related to what and how educational curriculum had been validated and enforceable. This paper discusses the factual condition of curriculum in Indonesia, including the background of curriculum change since the promulgation of National Education System, and also about the implementation of the concept of Competency Based Curriculum (CBC/KBK), Education Unit Level Curriculum (SBC) and Curriculum 2013. The results of this study indicate that changes of curriculum are necessary. Nonetheless, curriculum changes implemented should have strong fundamentals and careful planning; hence it does not confuse the policy makers in the area of education.